The Effect of Slow Stroke Back Massages on Anxiety among Primigravid Women - MR Bazrafshan; Z Ghorbani (Tehran University of Medical Sciences, 2010)
Background & Objective: Pregnancy is a situational crisis in women;aposs lives that is potentially related to anxiety. Massage, a kind of relaxation technique, is a non-pharmacological intervention for anxiety relief. Slow stroke back massage is an independent nursing procedure that is closely associated with the caring nature of nursing. This study aimed to assess the effect of slow stroke back massages on anxiety level among primigravid women in two clinics in Shiraz in 2007.Methods & Materials: In this clinical trial, 80 primigravid women aged 15-35 who were in the 3rd trimester of pregnancy were enrolled in the study. The participants were randomly allocated in the intervention and control groups. The intervention group received slow stroke back massage for 10 minutes in three consecutive mornings. Anxiety level was measured before and immediately after the intervention in both groups. Data were gathered using the state anxiety Spielberger questionnaire and were analyzed using Chi-square test, Fisher;aposs Exact test, Paired t-test, and Independent statistic test (t-test).Results: The means of the anxiety level were 51±6.6 and 49.90±6.6 at baseline in the intervention and control groups, respectively (P=0.460). After the intervention, the means of anxiety level were 48.18±6.52 and 51.50±7.39 in the intervention and control groups, respectively (P=0.036).Conclusion: According to the results, slow stroke back massage seems to be an effective nursing intervention for anxiety relief in primigravid women. It provides an opportunity for nurses to offer individualized and holistic patient care.